2021
DOI: 10.1186/s13287-021-02573-6
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles derived from mesenchymal stem cells as a potential therapeutic agent in acute kidney injury (AKI) in felines: review and perspectives

Abstract: Mesenchymal stem cells (MSCs), known from their key role in the regeneration process of tissues, and their abilities to release bioactive factors like extracellular vesicles (EVs) could be considered as a potential, modern tool in the treatment of AKI (acute kidney injury) in both human and veterinary patients. The complex pathophysiology of a renal function disorder (AKI) makes difficult to find a universal therapy, but the treatment strategy is based on MSCs and derived from them, EVs seem to solve this prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Blood transfusion of MSC-Exo can accumulate in injured tissues but is rapidly cleared within 24 hours by the liver and spleen. 33 As a result, neutrophils would be suppressed by MSC-Exo only at the acute pro-inflammatory phase in the initial time of I/R, which did not affect the subsequent repairment. In addition, the long-term pathological results demonstrated that the ventricular remodeling and fibrosis following I/R injury were both attenuated by MSC-Exo treatment, which showed a standing beneficial effect of MSC-Exo on the initial phase of myocardial I/R (in Figure 5 ).…”
Section: Discussionmentioning
confidence: 94%
“…Blood transfusion of MSC-Exo can accumulate in injured tissues but is rapidly cleared within 24 hours by the liver and spleen. 33 As a result, neutrophils would be suppressed by MSC-Exo only at the acute pro-inflammatory phase in the initial time of I/R, which did not affect the subsequent repairment. In addition, the long-term pathological results demonstrated that the ventricular remodeling and fibrosis following I/R injury were both attenuated by MSC-Exo treatment, which showed a standing beneficial effect of MSC-Exo on the initial phase of myocardial I/R (in Figure 5 ).…”
Section: Discussionmentioning
confidence: 94%
“…Since the stem cells are very dynamic, they can obtain Evs such as exosomes [ 129 ]. According to the mentioned applications of EVs, they can be used as nanoparticles in organoid models to make them more efficient [ 130 , 131 ]. EVs: extracellular vesicles …”
Section: Organoids As 3d Culture Models For Evs Analysismentioning
confidence: 99%
“…In a few previous studies about EVs in kidney-related disease ( Pisitkun et al, 2004 ; Zhou et al, 2006a ; Bruno et al, 2009 ; Gonzales et al, 2009 ; Miranda et al, 2010 ; van Balkom et al, 2011 ; Alvarez et al, 2012 ; Merino et al, 2014 ; Fais et al, 2016 ), it was shown that EVs are endogenous or natural membranous nanoparticles that play important roles in essentially all organisms; were used as drug carriers in nanomedicine; and were found to play important roles in the diagnosis, treatment, and prognosis of kidney-related diseases ( Kalluri and LeBleu, 2020 ; Lu and Huang, 2020 ; Fan et al, 2022 ; Tang et al, 2022 ; Yang et al, 2022 ). Recently, there have been increasing developments on EVs for the detection and treatment of more different types of kidney diseases, including CKD ( Sun et al, 2019 ; Tang et al, 2020a ; Grange et al, 2020 ; Jin et al, 2021 ; Grange and Bussolati, 2022 ; Tang et al, 2022 ; Wang et al, 2022 ), AKI ( Sun et al, 2019 ; Tang et al, 2020a ; Xie et al, 2020 ; Jin et al, 2021 ; Kraińska et al, 2021 ; Grange and Bussolati, 2022 ; Tang et al, 2022 ), lupus nephritis ( Thongboonkerd, 2019 ; Garcia-Vives et al, 2020 ; Xie et al, 2020 ; van Zonneveld et al, 2021 ; Grange and Bussolati, 2022 ), kidney-related inflammation ( Sun et al, 2019 ; Thongboonkerd, 2019 ; Tang et al, 2020a ; Tang et al, 2020b ; van Zonneveld et al, 2021 ), glomerular-related disorders ( Thongboonkerd, 2019 ; Jin et al, 2021 ; Grange and Bussolati, 2022 ), transplantation ( Thongboonkerd, 2019 ; Grange and Bussolati, 2022 ), diabetes ( Thongboonkerd, 2019 ; Grange and Bussolati, 2022 ; Tang et al, 2022 ), cancer ( Thongboonkerd, 2019 ; van Zonneveld et al, 2021 ), fibrosis ( Thongboonkerd, 2019 ;...…”
Section: Introductionmentioning
confidence: 99%